MODEL KULIAH WIRAUSAHA UNTUK BISNIS, EKSPORT TARNITARE - Sunaryo, Sunaryo - (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2003)
Amid economic courses situation and high number of employment caused by industries and  business  downsizing,  even bruncrupcies, therefore  it  is  necessary for students as intellectual people to be prepared not only for employed but also to be  self employed or (entrepreneurship).  The objective of this entrepreneurship course is in line with necessity above that students need to possess the knowledge, skill, attitudes, as well as a vision on entrepreneurship.The number of participants of the course were 36 students consists of 33 students from Building Construction Education  Study Program, one  student from Mechanical Study Program,  and  two  students  from  Educational  Faculty  in  University  State  of Yogyakarta. The course  was designed to educate students to master selecting material and-technical production in furniture production and how to market the furniture, especially to buyers in foreign countries. The methods were utilized in the course, such as lecture, demonstration, discussion, seminar, inviting professional business players/guest lecture, and field visit. The course consists of:  (1) Inspire the sole of Entrepreneurship, (2)  Strategy and  Efforts  in  Furniture  Business, (3)  ISO  14.000 &  Ecolabelling, (4) Selecting Row Material & Storage, (5) Business Plan: Situation analysis & Purpose of Business, (6) Proposing Capital to Bank for Small Business, (7) Strategy, Capital, and Marketing, (8)  Finishing  Process,  (9)  Break  Even  Point  &  Financial  Estimation  of Business, (10) Cash-flow, (11) Establishing Business, (12) Risk Management, (13) Business Ethics, (14) Business Presentation, and (15) Final Exam.The cause  accomplishment  would be valuable  contribution  to  the  institution, instructors and especially for the participated students who are still layman in the would of entrepreneurship. So far the students want to be government employees after their graduation. The course is expected provide the students insight especially in the furniture businesses.  Running  business  with  preparing  Business  Plan  will  minimize  the  risk, manage the business better and maximize profits. The indicators of the success of the course are such as : (1) The development of entrepreneurship class-note or module; (2) Business Plan and Its Presentation; and  (3) Most of the students would be ready to be new entrepreneurship.  Key words:  entrepreneurship course, and eksport  funiture